2014
DOI: 10.3368/er.32.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Heterogeneous Disturbance Regimes for the Preservation of Endangered Species

Abstract: Disturbance is a natural component of ecosystems. All species, including threatened and endangered species, evolved in the presence of, and are adapted to natural disturbance regimes that vary in the kind, frequency, severity, and duration of disturbance. We investigated the relationship between the level of visible soil disturbance and the density of four endangered plant species on U.S. Army training lands in the German state of Bavaria. Two species, gray hairgrass (Corynephorus canescens) and mudwort (Limos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…That was the main result of this research, and it will allow wildlife managers to better estimate the opportunity cost of establishing ESHs. Cost factors related to pattern differences interacted to determine the functionality of silvicultural prescriptions in creating viable wildlife habitats related to the elements known to influence endangered species populations like disturbance patterns [67], rotation age [26,68], and edges [69,70]. Often these frameworks are evaluated on a financial basis, and we presented a functional model to perform that type of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…That was the main result of this research, and it will allow wildlife managers to better estimate the opportunity cost of establishing ESHs. Cost factors related to pattern differences interacted to determine the functionality of silvicultural prescriptions in creating viable wildlife habitats related to the elements known to influence endangered species populations like disturbance patterns [67], rotation age [26,68], and edges [69,70]. Often these frameworks are evaluated on a financial basis, and we presented a functional model to perform that type of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Military training activities are known to impact individual species, and it has been shown that many rare and protected species across different parts of the world can benefit from these disturbances (Gazenbeek 2005, Warren & Büttner 2008, Warren & Büttner 2014, Kim et al 2015. The disturbance caused by military training activities may mimic natural disturbances for some species (Rivers et al 2010), and delay or prevent natural succession thus conserving vegetation communities in a state that would otherwise become overgrown with shrubs and trees if left undisturbed (Warren & Büttner 2008, Kim et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research in this field has been carried out in the USA. Very few studies have been undertaken in Europe (but see Gazenbeek 2005, Warren et al 2007, Warren & Büttner 2008, Warren & Büttner 2014 and we are unaware of any specifically in the north-eastern part of the Europe.…”
Section: Introductionmentioning
confidence: 99%